Customer Satisfaction Under Equal Access Environment In Telekom Malaysia - Nordin, Mohd Ali (2000)
Deregulation and technological innovation are drastically changing the structure of traditionally regulated telecommunication industries. Telekom Malaysia began to experience this critical environment change in its business handling in early 1999 with the government's introduction of the Communications and Multimedia Act covering its deregulation rules for the basic services known as Equal Access (EA).